The autopsy is not dead: ongoing relevance of the autopsy - Alexia Vignau; Clara Milikowski (University of São Paulo, 2023)
Background: Autopsy requests have been trending downward for a variety of factors. There are differences between pre- and postmortem diagnoses. Autopsies remain a tool for education, public health research, quality control, and closure for families. Objective: We report two cases that illustrate the utility of autopsy for uncovering contributing factors in the death of these patients and highlight their ongoing importance. Design: Clinical and autopsy investigation of two individuals and illustration of the importance of autopsy findings which, had they been diagnosed premortem, could have changed the outcome. Cases were evaluated using the Goldman criteria for discrepancies between premortem clinical diagnoses and postmortem autopsy findings. Results: In the first case, the patient had been previously admitted due to a non-ST elevation myocardial infarction months before the fatal event. The autopsy showed an undiagnosed clear cell carcinoma of the ovary. She expired due to a massive myocardial infarction secondary to neoplasm induced hypercoagulable state. The degree of pre-mortem/postmortem diagnostic discrepancy makes this a Goldman Class I error. In the second case, the patient presented to the emergency department with symptoms of Guillain-Barré Syndrome (GBS), for which he was treated. Abdominal masses were discovered; however, the patient decompensated before workup was completed. A high-grade B-cell lymphoma was confirmed but would not have altered the outcome, making this a Goldman class II error. Conclusions: The autopsy remains a relevant and necessary tool for physicians and society. It assists in the establishment of diagnoses, measurement of treatment quality, the providence of public health metrics, and closure to the survivors.